2020
DOI: 10.1111/1753-0407.13130
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiologically verified effects of acupuncture on diabetic peripheral neuropathy in type 2 diabetes: The randomized, partially double‐blinded, controlled ACUDIN trial

Abstract: Background: Acupuncture is commonly used in Traditional Chinese Medicine for treatment of diabetic peripheral neuropathy (DPN), but data from randomized controlled trials are rare.Methods: This randomized, placebo-controlled, partially double-blinded clinical trial randomly assigned adults with confirmed type 2 diabetes-induced DPN to receive 10 sessions of needle acupuncture, laser acupuncture, or placebo laser acupuncture for 10 consecutive weeks. Treatment was provided at bilateral acupoints Ex-LE-10 (Bafen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 42 publications
1
30
0
1
Order By: Relevance
“…As shown in a previous review, this can also lead to new technological systems to measure TCM-related effects, and to calibrate and mimic complex and skillful diagnosis procedures [ 211 ]. A second crucial factor is the further development of experimental approaches in TCM research, such as the double-blinding of acupuncture trials [ 120 , 134 , 135 , 136 , 137 ] and the development of a placebo for “Qigong” research [ 212 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in a previous review, this can also lead to new technological systems to measure TCM-related effects, and to calibrate and mimic complex and skillful diagnosis procedures [ 211 ]. A second crucial factor is the further development of experimental approaches in TCM research, such as the double-blinding of acupuncture trials [ 120 , 134 , 135 , 136 , 137 ] and the development of a placebo for “Qigong” research [ 212 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that major effects of acupuncture have now also been confirmed by prospective randomized and even double-blinded clinical trials [ 120 , 134 , 135 , 136 , 137 ].…”
Section: Acupuncture Moxibustion and Cuppingmentioning
confidence: 99%
See 1 more Smart Citation
“…A sensory nerve conduction study (NCS) revealed that acupuncture increased the nerve conduction velocity (NCV) in the median and peroneal nerves. In a recently published RCT, 172 patients with diabetic neuropathy received 10 acupuncture treatments or 10 laser acupuncture or 10 placebo laser treatments; sural SNAP and sural and tibial NCV improved significantly when comparing needle acupuncture to placebo [12]. Neuropathies with different etiology have been investigated in the past.…”
Section: Background and Rationale {6a}mentioning
confidence: 99%
“…A sensory nerve conduction study (NCS) revealed that acupuncture increased the nerve conduction velocity (NCV) in the median and peroneal nerves. In a recently published RCT, 172 patients with diabetic neuropathy received 10 acupuncture treatments or 10 laser acupuncture or 10 placebo laser treatments; sural SNAP and sural and tibial NCV improved signi cantly when comparing needle acupuncture to placebo [12]. Neuropathies with different etiology have been investigated in the past.…”
mentioning
confidence: 99%